Ambiguity : language and communication - Winkler, Susanne, 1960- (Berlin : De Gruyter, 2015)
'This volume uncovers a great mystery about language: why can we communicate so effectively despite the fact that ambiguity is pervasive? Conversely, how do speakers use ambiguity to achieve a specific goal? Answers to these questions are provided from different fields: (psycho)linguistics, literary criticism, rhetoric, theology, media studies, [and] law'--
Part III: (Strategic) Ambiguity in the Perception ProcessAmbiguity and Sentence Position: An Experimental Case Study on Manner Adverbs; The Influence of Prosody on Children's Processing of Ambiguous Sentences; Discourse Function Ambiguity of Fragments: A Linguistic Puzzle; Ambiguiteat und Schriftauslegung: Beobachtungen zu Augustins Schrift De utilitate credendi; Part IV: (Strategic) Ambiguity in Communicative Interaction; Dimensions of Constitutive Ambiguity; Ambiguity in Speaker-Hearer-Interaction: A Parameter-Based Model of Analysis.
Essays proceeding from an international symposium,'Dimensions of Ambiguity', held at Tubingen, Germany in 2009.
Includes bibliographical references and index.
Foreword in German; introduction in English ; articles in German and English.
Keywords: Ambiguity -- Congresses; Semantics -- Congresses; Psycholinguistics -- Congresses